The future of management education. Volume 1, - Dameron, Stéphanie; Durand, Thomas (Palgrave Macmillan, 2017)
This book discusses the new challenges facing Business Schools around the world with potential scenarios that may be envisioned for 2030 and strategies for stakeholders. Based on documented descriptions of competitive dynamics in the 'business' of business schools in a variety of countries, the authors highlight the fact that the 'industry' of management education is going through major changes such as new governance and business models, mergers and acquisitions, internationalization of faculty and students coexisting with entrenchment in local markets, ever more needs for financial resources, development of distant and blended learning, and increasing pressure for research output to boost rankings. With concerns surrounding the sustainability of current trends in faculty salary inflation, social acceptability of higher fees, cost of distance learning and the risk of an academic-industry divide around knowledge produced by management research, The Future of Management Education develops an analysis of business models and institution regulation. The two volumes cover the context of Business Schools in ten countries and grapples with the challenges they currently face. They specifically discuss foresight scenarios and strategic implications for stakeholders (Deans, faculty, students, prospective students, alumni, local businesses, corporations, government, accreditation bodies).- Resué vydavatel